Characterization of poultry litter ashes as a supplementary cementitious material. (December 2022) - Castillo, D.; Cruz, J.C.; Trejo-Arroyo, D.L.; Muzquiz, E.M.; Zarhri, Z.; Gurrola, M.P.; Vega-Azamar, R.E.
Abstract: In the present work, the possibility of using poultry litter ash (PLA) as a supplementary cementing material (SCM) is presented. Its physicochemical and microstructural parameters were determined and correlated to compressive strength. Thermogravimetric analysis (TGA) determined three suitable treatment temperatures and its training products. XRF analysis showed CaO, P2 O5 and SiO2 as the main components. XRD confirmed the presence of calcite, anhydrite and quartz at 600–700 °C, and weddellite formation at higher temperatures (800 °C). SEM results corroborated the formation of crystals, favoring the formation of weddellite and the presence of ettringite at higher temperatures. Pozzolanic activity was evaluated through the Strength Activity Index (SAI). PL calcined at 800 °C showed a SAI 60.71% higher than the rest studied. Cement substitutions for PLA calcined at 800 °C were tested at 10%, 15% and 20% by evaluating compressive strength at 90 days of curing. The best performance was observed for the 10% replacement. All three percentages of substitution, exceeded a SAI value of 75%, according the ASTM C-618 standard. Highlights: Poultry litter ash as supplementary cementitious material. Poultry litter ash characterization. Cement substitution. Strength Activity Index.